Solar-induced 27-day modulation on polar mesospheric cloud (PMC), based on combined observations from SOFIE and MLS - Qiu, Shican; Yuan, Mengzhen; Soon, Willie; Velasco Herrera, Victor Manuel; Zhang, Zhanming; Yang, Chengyun; Yousof, Hamad; Dou, Xiankang (Frontiers in Astronomy and Space Sciences, 2023)
Temperature and water vapor are two key variables affecting the polar mesospheric cloud (PMC). Solar radiation can increase the mesospheric temperature through UV heating. In this research, the composite solar index Y10 is used for the first time to study the influence of solar radiation on PMC variability. The ice water content (IWC) is selected to characterize the properties of PMCs. The observations of IWC are from the Solar Occultation For Ice Experiment (SOFIE) onboard the Aeronomy of Ice in the Mesosphere (AIM) satellite, and the temperature data used are measured by both the SOFIE instrument and Microwave Limb Sounder (MLS) onboard the Aura satellite. According to the superposed epoch analysis (SEA) method, it is shown that the solar 27-day modulation can affect PMCs by changing and modulating the mesospheric temperature. The results show that the IWC responds to the Y10 later than the mesospheric temperature does. Further investigation into the relationship between the mesospheric temperature and PMCs reveals that the average time lag is 0 days in the northern hemisphere (NH) and 1 day in the southern hemisphere (SH). The differences in temperature response to the 27-day solar rotational modulation with atmospheric pressure and latitude are also analyzed on the basis of the temperature observations made from 2004 to 2020 by the MLS. The temperature time lag of NH2008 and NH2012 are 1–5 days (depending on latitude), close to the time lag of direct solar heating with 4 days. The PMC seasons with temperature time lags greater than 5 days are indicated to be modulated by atmospheric dynamics with a 27-day cycle. The temperature time lag has two distinct patterns of variation in latitude, and thus two different atmospheric modulation mechanisms may exist. Twelve PMC seasons with 27-day periodicity are distinguished, nine of which have decreasing temperature time lags with increasing altitude because of the atmospheric dynamical effects.